The history of Texas music - Hartman, Gary (John and Robin Dickson series in Texas music., 2008)
"The richly diverse ethnic heritage of the Lone Star State has brought to the Southwest a remarkable array of rhythms, instruments, and musical styles that have blended here in unique ways and, in turn, have helped shape the music of the nation and the world." "Historian Gary Hartman writes knowingly and lovingly of the Lone Star State's musical traditions. In the first thorough survey of the vast and complex cultural mosaic that has produced what we know today as "Texas music," he paints a broad, panoramic view, offers analysis of the origins of and influences on specific genres, profiles key musicians, and provides guidance to additional sources for further information." "A musician himself, Hartman draws on both academic and non-academic sources to give a more complete understanding of the state's remarkable musical heritage. He combines scholarly training in music history and ethnic community studies with his first-hand knowledge of how important music is as a cultural medium through which human beings communicate information, ideas, emotions, values, and beliefs, and bond together as friends, families, and communities." "The History of Texas Music incorporates a selection of well-chosen photographs of both prominent and less-well-known artists and describes not only the ethnic origins of much of Texas music but also the cross-pollination among various genres. Today, the music of Texas - which includes Native American music, gospel, blues, ragtime, swing, jazz, rhythm and blues, conjunto, Tejano, cajun, zydeco, western swing, honky tonk, polkas, schottisches, rock & roll, rap, hip hop, and more - reflects the unique cultural dynamics of the Southwest."--Jacket